Undiagnosed tuberculosis associated with hemophagocytic lymphohistiocytosis due to improper use of corticosteroid - Allahverdi Nazhand, Hadi; Sabeti, Shahram; Javandoust Gharehbagh, Farid; Nalini, Ronak; Babamahmoodi, Abdolreza; Marahemi, Maryam; Mahmoudi Chalmiani, Elmira; Lotfollahi, Legha; Alavi Darazam, Ilad (The Journal of Infection in Developing Countries, 2023)
Introduction: Hemophagocytic lymphohistiocytosis (HLH) is a rare and life-threatening hematologic disease segregated into familial (primary) and acquired (secondary) subtypes. Hyperinflammation and HLH occur when the immune system fails to clear activated macrophages and histiocytes. Infections, malignancies, and rheumatologic disorders are the major triggers leading to HLH. Miliary tuberculosis is a serious disease with a lymphohematogenous spread of Mycobacterium tuberculosis, which is known to be one of the causative agents of HLH. Miliary tuberculosis and HLH have atypical presentations which are similar to routine diseases. Hence, physicians may face challenges to diagnose and treat these complications. Case report: We report the case of a 60-year-old man with a history of prolonged fever, shortness of breath, jaundice, altered mental status, undiagnosed lower back pain, and overuse of parenteral betamethasone. Miliary tuberculosis was diagnosed by diffuse, vague random micronodules in both lungs and positive acid-fast bacilli in bronchoalveolar lavage and bone marrow aspiration and biopsy. Moreover, compatible presentation and pancytopenia, hypertriglyceridemia, high serum level of ferritin and fibrinogen-derived products, and evidence of hemophagocytosis on bone marrow aspirate led to the diagnosis of HLH. Unfortunately, despite nearly two months of an anti-tuberculosis regimen (standard and salvage) and eight doses of etoposide, he eventually passed away after clinical improvement. Conclusions: Irrational and indiscriminate use of glucocorticoids can be a devastating cause of the spread of tuberculosis and its rare complications, such as HLH.